2017
DOI: 10.1111/ans.14268
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing lymph node skip metastasis in colorectal cancer: a retrospective study

Abstract: pT1-2 stage and pN1 stage are significantly associated with LNSM. Radical D3 lymphadenectomy should remain standard practice for CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…[7][8][9] In relatively rare conditions, lymph node metastasis occurs at nodes far from the primary tumor with pericolic or intermediate nodes sparing, and this has been referred to as lymph node skip metastasis (LNSM) in previous literature. [6][7][8][9][10][11] LNSM has been described in gastric cancer, 12,13 thyroid cancer, 14,15 lung cancer, 16,17 and breast cancer, 18,19 with either a positive or negative impact on survival in line with different tumor types. However, there are few studies that have investigated the prognostic role of LNSM in lymph node-positive colon cancer.…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] In relatively rare conditions, lymph node metastasis occurs at nodes far from the primary tumor with pericolic or intermediate nodes sparing, and this has been referred to as lymph node skip metastasis (LNSM) in previous literature. [6][7][8][9][10][11] LNSM has been described in gastric cancer, 12,13 thyroid cancer, 14,15 lung cancer, 16,17 and breast cancer, 18,19 with either a positive or negative impact on survival in line with different tumor types. However, there are few studies that have investigated the prognostic role of LNSM in lymph node-positive colon cancer.…”
Section: Principales Medidas De Resultadomentioning
confidence: 99%
“… 23 , 37 Third, the local effect of the primary tumor may block pericolic lymphatic drainage. 11 Fourth, lymph node degeneration in patients who are elderly may facilitate skip metastasis. 38 , 39 Thus, further studies are necessary to clarify the true causes and tumor biology of LNSM.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with LNSM tend to have smaller tumor diameters and shallower tumor invasion than patients in the skipnegative group [12]. Previous studies have found that patients with LNSM have a better prognosis than patients without LNSM after radical D3 lymphadenectomy [11,13]. Because the presence of TDs has a poor prognosis, it seems contradictory that TDs can result in skip metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In the TNM stage of colon cancer after surgery, pT1-2 and pN1 are independent risk factors for skipping metastasis in colon cancer. [10] 2.4 Tumor staging TNM staging, proposed by Pierre Denoix, is a commonly used clinical staging method for epithelial malignancies. Clinically, T, N and M indicate primary tumor lesion, lymph node involvement and distant circulatory metastasis respectively.…”
Section: Mode Of Lymph Node Metastasismentioning
confidence: 99%
“…According to the 2019 Guidelines for the Treatment of Colorectal Cancer compiled by the Japanese Colon and Rectal Cancer Association (JSCCR), [10] it is emphasized that lymph nodes should be thoroughly dissected at the peribowel, mesentery, and mesenteric artery roots at the same time as colon cancer lesions are resected. In surgery, the degree of lymph node dissection is determined based on the clinical diagnosis and the likelihood of lymph node metastasis observed during surgery.…”
Section: D3 Colon Cancer Radical Surgerymentioning
confidence: 99%